2000
DOI: 10.1210/mend.14.6.0485
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine Tract-Binding Protein-Associated Splicing Factor Is a Negative Regulator of Transcriptional Activity of the Porcine P450scc Insulin-Like Growth Factor Response Element

Abstract: The porcine P-450 cholesterol side-chain cleavage enzyme gene (P450scc) contains a 30-bp region [insulin-like growth factor response element (IGFRE)] that mediates insulin-like growth factor I (IGF-I)-stimulated gene expression and binds Sp1. In this study, we showed that polypyrimidine tract-binding protein (PTB)-associated splicing factor (PSF), an RNA-binding component of spliceosomes, binds to the IGFRE. Southwestern analysis with an IGFRE oligonucleotide showed that a protein (from Sp1-immunodepleted HeLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…www.pnas.org͞cgi͞doi͞10.1073͞pnas.0508805102 (2,3). We reported that PSF also represses oncogenic genes (OG), and that retroviral-mediated transfection of VL30 retroelement RNA into a human nonmetastatic tumor line formed a PSF-VL30 RNA complex that reversed repression by PSF and promoted metastasis (4,5).…”
mentioning
confidence: 99%
“…www.pnas.org͞cgi͞doi͞10.1073͞pnas.0508805102 (2,3). We reported that PSF also represses oncogenic genes (OG), and that retroviral-mediated transfection of VL30 retroelement RNA into a human nonmetastatic tumor line formed a PSF-VL30 RNA complex that reversed repression by PSF and promoted metastasis (4,5).…”
mentioning
confidence: 99%
“…PSF represses the porcine gene P450scc, by binding to the IGFRE motif in the gene (5,6). Our finding that mVL30-1 RNA induces transcription of the homologous human P450scc gene (Table 1) and forms a complex with PSF (Fig.…”
Section: Mapping the Tracts In Mvl30-1 Rna That Form A Complex With Psfmentioning
confidence: 73%
“…The protein was originally identified as a component of spliceosomes (3) and later shown to function as a repressor of the IGF1-inducible gene P450ssc, which controls a rate-limiting step in steroid synthesis (5). Repression of P450scc involves binding of PSF to an IGFRE motif of the gene (5), and the complex formed with mVL30-1 RNA inhibits and dissociates the binding of PSF to the IGFRE (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In some cases, higher values may be calculation artifacts due to an uneven gel run, with this effect being relatively greater in the high molecular weight region of gels. In others, they are due to an anomalous migration on SDS-PAGE due to intrinsic characteristics of the molecule, as is the case for PTB-associated splicing factor 22 and moesin. 23 Function analysis (Figure 4) shows that the proteins identified are distributed among the following groups: cytoskeleton/ migration (24.7%), metabolism (17.6%), granule secretory components (11.3%), gene regulation (10.3%), protein synthesis/ modification/degradation (7.2%), membrane fusion/trafficking (6.2%), chaperones and protein folding (5.2%), redox (4.1%), bactericidal mechanisms (4.1%), signaling (3.1%), calciumbinding (3.1%) and receptors (1.0%).…”
Section: Separation Of Proteins From Whole Eosinophil Extracts and Cymentioning
confidence: 99%